Visual Inspection of Acetic Acid (VIA) as a Promising Standard for Cervical Cancer Screening - Utami, Tofan W (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To evaluate the "false negative" of VIA in our study population compared to HPV DNA test as the reference test or gold standard. Method: We processed the cervical swab from 1,279 patients with negative VIA and detected the HPV DNA by using INNO-Lipa HPV DNA test. Result: From 1,279 women with negative VIA, 65 samples were excluded because of incomplete data and duplicate examination. From the remaining 1,214 women with negative VIA, 39 samples were confirmed to be positive for HPV DNA by both PCR and hybridization, leading to a "false negative" result of 3.21%. Conclusion: This study shows VIA as a very effective method for cervical cancer screening. VIA gives an excellent result, particularly for ectocervix, with minimal cost. Therefore, it is very suitable to be used as cervical cancer screening in developing countries like Indonesia. [Indones J Obstet Gynecol 2014; 4: 216-219] Keywords: cervical cancer, HPV DNA, negative VIA, screening, VIA